Abstracts Presented at the Conquering Heart Disease in the Himalayan Region International Conference 16-17 October 2011 - Editor, The (Nepalese Heart Journal, 2013)
DOI: http://dx.doi.org/10.3126/njh.v8i1.8337 Nepalese Heart Journal Vol.8(1) 2011 pp.43-52